Effect of Early Use of Botulinum Toxin A on Goal Attainment in Post-Stroke Spasticity - Atul Patel; Jinming Zhang; Simon Page; Sarah Harding; Mathieu Beneteau; Alberto Esquenazi (Toxicon, 2026)

Temporal and Spatial Dynamics of Synechococcus Clade II and Other Microbes in the Eutrophic Subtropical San Diego Bay - Katie J. Harding; Maitreyi Nagarkar; Maggie Wang; Kailey Ramsing; Niv Anidjar; Sarah Giddings; Bianca Brahamsha; Brian Palenik (Environmental Microbiology, 2025)
The diversity of the marine cyanobacterium Synechococcus can be broadly separated into clades, with clade II typically present in warm oligotrophic water, and clades I and IV found in cooler coastal water. We found amplicon sequence variants (ASVs) belonging to clade II in the nutrient‐replete waters of San Diego Bay (SDB). Using the 16S rRNA gene, 18S rRNA gene and internal transcribed spacer region sequencing, we analysed multiple locations in SDB monthly for over a year, with additional samples dating back to 2015. Synechococcus community composition differed from the nearby coast into SDB in terms of dominant clade and ASVs. Specific clade II ASVs became relatively more abundant towards the back of the bay and showed seasonality, with higher relative abundance in the warm months. Select ASVs group phylogenetically and show similar seasonal and spatial distribution patterns, indicating these ASVs have adapted to SDB. Isolates matching clade II ASVs from SDB show pigment composition that is better adapted to the green light available in SDB, further supporting our findings. Other microbial taxa also show SDB enrichment, providing evidence that SDB is a chemostat‐like environment where circulation, temperature, light and other environmental conditions create a zone for microbial evolution and diversification.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

The Fourth Global Coral Bleaching Event: Where do we go from here? - James Davis Reimer; Raquel S. Peixoto; Sarah W. Davies; Nikki Traylor-Knowles; Morgan L. Short; Rafael A. Cabral-Tena; John A. Burt; Igor Pessoa; Anastazia T. Banaszak; R. Scott Winters; Tom Moore; Verena Schoepf; et al. (Coral Reefs, 2024)

High-altitude characterization of the Hunga pressure wave with cosmic rays by the HAWC observatory - Ruben Alfaro; César Alvarez; Juan Carlos Arteaga-Velázquez; Arun Babu Kollamparambil Paul; Daniel Avila Rojas; Hugo Alberto Ayala Solares; Rishi Babu; Ernesto Belmont-Moreno; Chad Brisbois; Karen S. Caballero-Mora; Tomás Capistrán; Alberto Carramiñana; et al. (Advances in Space Research, 2024)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Epidemiology, Clinical Features, and Management of Texas Coral Snake (Micrurus tener) Envenomations Reported to the North American Snakebite Registry - Spencer Greene; Anne-Michelle Ruha; Sharan Campleman; Jeffrey Brent; Paul Wax; Kim Aldy; Peter Akpunonu; Vikhyat S. Bebarta; Gillian A. Beauchamp; Michael C. Beuhler; Mary Billington; William Boroughf; et al. (Journal of Medical Toxicology, 2021)

Faecal indicator bacteria in New Zealand freshwater fish: a pilot study - Sarah Coxon; Jon S Harding; Brent Gilpin (New Zealand Journal of Marine and Freshwater Research, 2019)
Recent studies have suggested that poikilothermic animals, such as fish, may represent a previously overlooked source of the faecal indicator bacteria (FIB) used for the assessment of water quality. However, quantitative studies of FIB in poikilotherms are scarce. We investigated the presence of FIB in the faeces of five freshwater fish species. E. coli and enterococci were detected in 71 and 76% of faecal samples, respectively. Concentrations were highly variable, with maximum concentrations (2.1 × 10 4 E. coli and 1.3 × 10 6 enterococci per gram of faecal material) up to four orders of magnitude higher than present in the water column. FIB were not detected in faecal samples from marine fish. Our findings suggest that FIB ingested from the environment may be capable of replication within the fish gut, making fish a potential source and transport mechanism for FIB in New Zealand freshwaters. This may have implications for water quality monitoring.

Human Dimensions / Recreation and Ecotourism - Rachel Billingham; Marissa Jo Daniel; Francisco Aguilar; Hank Stelzer; Guy Robertson; Stanley Asah; Michelle King; Angela Gupta; Samatha Grant; Christopher Jones; Melanie Lenart; Richard Tholen; et al. (Journal of Forestry, 2011)
8With the current state of the economy and the budget woes found in everyone's workplace, every extra dollar we can use to offset the cost of projects counts—and what if those extra dollars came with public relations opportunities at no cost to you? For the last several years, the Pennsylvania Bureau of Forestry has cultivated relationships with a variety of non-traditional partners. These relationships have not only provided additional funds for tree planting projects through our TreeVitalize program, but have also provided fantastic public relations exposure and access to new audiences. Come hear how we used a “win-win” approach with our new partners and be inspired to try some of these ideas in your “neck of the woods.”